Innovation, CSR, Work Environment, Company Reputation Financial Performance with Strategic Objectives as Mediation Variables - Mutia Rizky Septiani; Tubagus Ismail; Munawar Muclish (PT. EQUATOR SINAR AKADEMIA, 2022)
Financial performance, one of which is in the financial sector. The decline in financial performance, during the COVID-19 pandemic, could be caused by a decline in the debtor's financial condition, late payments and other payment problems, as well as the deteriorating business prospects of creditors. Which results in a decline in credit quality or the occurrence of bad loans which will have an impact on the decline in banking financial performance. In this case, the disbursement of credit in a larger amount compared to customer deposits will cause banks to face liquidity risk which will lead to a decline in banking financial performance. The COVID-19 pandemic has not only impacted the financial performance of the banking sector, but also the performance of companies financing, one of which is fintech. Thus, giving rise to various services in the field of financial services by utilizing modern technology that provides services in the form of payments, lending money, investments, transfers